2000
DOI: 10.1038/sj.bjp.0703061
|View full text |Cite
|
Sign up to set email alerts
|

Impaired relaxation of stomach smooth muscle in mice lacking cyclic GMP‐dependent protein kinase I

Abstract: 1 Guanosine 3', 5'-cyclic monophosphate (cyclic GMP)-dependent kinase I (cGKI) is a major receptor for cyclic GMP in a variety of cells. Mice lacking cGKI exhibit multiple phenotypes, including severe defects in smooth muscle function. We have investigated the NO/cGMP-and vasoactive intestinal polypeptide (VIP)/adenosine 3', 5'-cyclic monophosphate (cyclic AMP)-signalling pathways in the gastric fundus of wild type and cGKI-de®cient mice. 2 Using immunohistochemistry, similar staining patterns for NO-synthase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 26 publications
2
49
0
Order By: Relevance
“…10 PRKG1 knockout mice have a decreased lifespan, defects in relaxation of vascular, visceral, and penile smooth muscle, disturbed platelet adhesion and activation, and impaired guidance of sensory axons during embryogenesis. 11,12 The NO/cGMP pathway, where PRKG1 is one of the downstream players, mediates regulatory effects on key enzymes of fatty acid synthesis and oxidation and may be involved in physiological control of fatty acid metabolism in liver. 13 Leptin-deficient obese mice show significant changes in NO/cGMP signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…10 PRKG1 knockout mice have a decreased lifespan, defects in relaxation of vascular, visceral, and penile smooth muscle, disturbed platelet adhesion and activation, and impaired guidance of sensory axons during embryogenesis. 11,12 The NO/cGMP pathway, where PRKG1 is one of the downstream players, mediates regulatory effects on key enzymes of fatty acid synthesis and oxidation and may be involved in physiological control of fatty acid metabolism in liver. 13 Leptin-deficient obese mice show significant changes in NO/cGMP signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…62,127,[191][192][193][194][195][196][197] Numerous studies have shown responses to NO in the GI tract depend upon the production of cyclic GMP (cGMP) by soluble guanylate cyclase. [198][199][200] Guanylate cyclase is a heterodimer comprised of 2 subunits, α and β. Using immunohistochemistry Iino et al 182,201 showed that both subunits are strongly expressed in ICC but not resolved in smooth muscle.…”
Section: Functional Evidence Demonstrating the Importance Of Interstimentioning
confidence: 99%
“…NO elicits hyperpolarization and relaxation responses in GI muscles, and these responses depend upon generation of cGMP and cGMP dependent protein kinase. 199,200,220 The proteins that mediate membrane hyperpolarization are debated, and some investigators have viewed the hyperpolarization response to be due to activation of a K + conductance [231][232][233] while others have suggested the response is due to suppression of an inward current due either to a non-selective cation conductance 206 or a chloride conductance. 234 Resolution of these questions and determining which of the cells in the SIP syncytium express the specific types of ion channels responsible for responses to NO will require additional experimentation.…”
Section: Evidence Opposing a Role For Interstitial Cells Of Cajal In mentioning
confidence: 99%
See 1 more Smart Citation
“…They target different components of the contractile signaling pathways that attenuate MLCK activity and/or augment MLC phosphatase (MLCP) activity, which eventually induce dephosphorylation of MLC 20 and thus smooth muscle relaxation (7,30,32,43). Although generation of both nucleotides and activation of both kinases are the physiological norm, dysfunctions of gastrointestinal motility in vivo and nitrergic relaxation in vitro in mice lacking neuronal NO synthase (nNOS), soluble guanylyl cyclase (sGC), or PKG-I suggest an important role for cGMP signaling in smooth muscle relaxation (5,11,27,35).The levels of cAMP and cGMP in gastrointestinal smooth muscle depend on the rates of their synthesis by cyclases and degradation by phosphodiesterases (PDEs) (3,8,10,29,40). cAMP is rapidly degraded by the cAMP-preferring PDE3 and cAMP-specific PDE4 (10, 33).…”
mentioning
confidence: 99%